DAYA HAMBAT ENZIM TIROSINASE DARI FORMULASI SEDIAAN HAND SANITZER GEL SEBAGAI ANTIAGING BERBAHAN AKTIF TANAMAN KOMODITAS HORTIKULTURA BERUPA KOMBINASI EKSTRAK BUAH NAGA MERAH DAN BUAH LEMON - Tri Yudianto; Arti Wahyu Utami; Rifkarosita Putri Ginaris; Nai’matul Retno Faizah; Octaviana Dyah Oentari; Alfina Nurrahman; Fitria Eka Resti Wijayanti; Sukardi Sugeng Rahmad; Reni Purbanova (Jurnal Kesehatan Tujuh Belas (Jurkes TB), 2022)
One of the long-term losses in homeostatic balance for any organism is a sign of aging skin. The state of hyperpigmentation caused by the activity of the tyrosinase enzyme is an indicator of aging. The solution that can be recommended to prevent premature signs of aging is by caring for the skin using the most affordable pharmaceutical preparation, namely Hand Sanitizer Gel. Hand Sanitizer Gel which has anti-aging properties can be produced from bioactive compounds from horticultural commodity plants because it has been proven and is quite popular. Apart from being able to be used as an active ingredient in functional food, it can also be used as a pharmaceutical, namely the preparation of active cosmetic ingredients. This is due to the content of vitamins, antioxidants, essential oils, proteins, even phenolic compounds and other environmentally friendly active ingredients found in horticultural commodity plants, especially the fruit group used in this research. Red dragon fruit has been proven to contain organic compounds such as gallic acid, elagic acid and ferulic acid which can inhibit the melanogenesis process both in vitro and in vivo from the results of previous findings. Lemons contain saponins, flavonoids, alkaloids and tannins so they can be designed to inhibit the tyrosinase enzyme. This research aims to determine the inhibitory power of the tyrosinase enzyme from extracts of horticultural commodity plants, both red dragon fruit and lemon peels in the form of hand sanitizer gel formulations and preparations. The results of this research have proven that based on the IC50 value, horticultural commodity plant extracts from lemon peel have better inhibitory power for the tyrosinase enzyme compared to red dragon fruit, namely 3,509 µg/mL. The conclusion in this research is that horticultural commodity plants in the form of lemon peel extract are more recommended as an active substance in inhibiting the tyrosinase enzyme when compared with red dragon fruit extract based on the IC50 value even though the hand sanitizer gel dosage form has the potential to inhibit the tyrosinase enzyme.